Iron acquisition by the genus mycobacterium : history, mechanisms, role of siderocalin, anti-tuberculosis drug development - Byers, B. Rowe (SpringerBriefs in Molecular Science, 2013)
Iron Acquisition by the Genus Mycobacterium summarizes the early evidence for the necessity of iron in mycobacteria and the discovery of the mycobacterial siderophores mycobactin, carboxymycobactin, and exochelin. The structural characterization of the mycobacterial siderophores is described.  The genes so far identified as essential for iron acquisition and maintenance of an infection by pathogenic mycobacteria are discussed.  The potential role of siderocalin in iron gathering by M. tuberculosis is featured. Because new drugs for M. tuberculosis are needed, this brief also emphasizes the design of antibiotics that interfere with siderophore biosynthesis and the use of siderophore analogs and/or conjugates.